The Ombudsmen in New Zealand by Bryan Gilling - Vosburg, William W (Victoria University of Wellington Law Review, 2000)
This article is a book review of Bryan Gilling The Ombudsman in New Zealand (Dunmore Press in association with the Historical Branch, Department of Internal Affairs, Palmerston North, 1998) (190 pages, 29.95). Gilling’s book provides an important account of the evolution of the New Zealand ombudsman providing an accessible and careful analysis of its first thirty years, which contained periods of both government stability as well as radical changes in the government’s structure, the economy, the class structure, the status of minority groups and foreign relations. Vosburgh states that the book stands as a study of institutionalism and evolution of government structures, and praises Gilling for containing a comprehensive account with a compact and sharp focus.